A novel ZIC3 mutation in a Chinese family with heterotaxy and multiple types of congenital heart defect. (30th December 2022) - Wang, Yu; Dai, Xiaohui; Liu, Hanmin; Peng, Jin; Chen, Jiao
Abstract: Aims: A couple was referred for prenatal counseling at gestational age 21 weeks for revealed situs inversus with levocardia (HP:0, 031, 592), atrial situs inversus (HP:0, 011, 538), congenitally corrected transposition of the great arteries (ccTGA, HP:0, 011, 540) with ventricular septal defect (HP:0, 001, 629) and right aortic arch (HP:0, 012, 020). The couple had multiple prior pregnancies with complex congenital heart defects (CHDs, HP:0, 001, 627) in male fetuses. Testing was initiated to identify any fetal abnormality. The genetic cause of the observed prenatal defects was investigated. Materials and Methods: Whole exome sequencing and Sanger sequencing were performed on DNA extracted from parental blood samples and skeletal muscle tissue of the aborted fetuses. Results: A pathogenic hemizygous missense variant in ZIC3 (NM_003413.4: c.895 T > C) associated with X‐linked heterotaxy‐1 (HTX1) and multiple types of congenital heart defect‐1 (CHTD1) (OMIM #306955) was identified, which was inherited from the mother. Conclusion: ZIC3 encodes a highly conserved zinc‐finger protein that is highly correlated with CHDs. The present study of a Han Chinese family with CHDs expands the mutation spectrum of ZIC3 and provides further evidence that ZIC3 plays important roles in CHDs. Key points: What is already known about this topic? The ZIC3 gene is located at Xq26.2, which is the location of the genetic cause of X‐linked heterotaxy (OMIM #306955). ZIC3 regulates early embryonic patterning in vertebrates and has critical roles during both gastrulation and embryonic cardiac development. What does this study add? A novel hemizygous mutation (c.890 G > T, p.C297 F) in ZIC3 was identified in a Han Chinese family with congenital heart defects, which expands the mutation spectrum of ZIC3 .